Health Care Seeking Behavior among the Parents for their Autistic Children (Journal of Current and Advance Medical Research, 2023)
Background: Autism Spectrum Disorders (ASD) are increasing alarmingly in recent times.Objective: The purpose of the present study was to find out the pattern of health care seeking behavior of the parents for their autistic children.Methodology: This cross-sectional study was conducted at Centre for Neurodevelopment and Autism in Children at Bangabandhu Sheikh Mujib Medical University, Dhaka from January to December 2013. The respondents were the parents of autistic children who came to the centres with their children.Results: About 61(66.3%) cases were in 2 to 6 years of age. Among the siblings, 8(8.7%) had autism and relatives of 8(8.7%) children had other developmental disorder. It is revealed that 67(72.8%) consulted specialist doctor, 23(25%) attended special teacher in scientific center. As many as 65(70.7%) were aware about autism and 80(87%) knew about the services provided at scientific centers. About 36(39.1%) had barriers to attend scientific centers. Lack of awareness (18 out of 36) was the most important barrier. Majority of the parents (79.3%) attended regularly to the health care centers for follow up.Conclusion: In conclusion raising awareness, dissemination of information, knowledge about autism including its risk factors and decentralization of health care facilities can overcome the impediment of getting appropriate health care.Journal of Current and Advance Medical Research, July 2022;9(2):83-90